2006
DOI: 10.1177/105971230601400103
|View full text |Cite
|
Sign up to set email alerts
|

Movement Models from Sports Provide Representative Task Constraints for Studying Adaptive Behavior in Human Movement Systems

Abstract: Researchers studying adaptive behavior in human movement systems have traditionally employed simplified, laboratory-based movement models in an effort to conserve experimental rigor. Brunswikian psychology raises questions over the representativeness of many of these popular experimental models for studying how movements are coordinated with events, objects, and surfaces of dynamic environments. In this article we argue that sports provide rich ecological constraints for representative task design in modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
0
19

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 146 publications
(154 citation statements)
references
References 75 publications
(81 reference statements)
4
129
0
19
Order By: Relevance
“…Such observations highlight the need to adequately sample environmental constraints in experimental designs to understand functional human behavior. This view has been expressed in a broad spectrum of research contexts, including motor coordination (Davids, Button, Araújo, Renshaw, & Hristovski, 2006), judicial contexts (Bradford & Goodman-Delahunty, 2008), marketing (Fasolo, Hertwig, Huber, & Ludwig, 2009), and medical education (Wigton, 2008).…”
mentioning
confidence: 99%
“…Such observations highlight the need to adequately sample environmental constraints in experimental designs to understand functional human behavior. This view has been expressed in a broad spectrum of research contexts, including motor coordination (Davids, Button, Araújo, Renshaw, & Hristovski, 2006), judicial contexts (Bradford & Goodman-Delahunty, 2008), marketing (Fasolo, Hertwig, Huber, & Ludwig, 2009), and medical education (Wigton, 2008).…”
mentioning
confidence: 99%
“…Today, they are not, and the empirical research reviewed here indicates a convergence to a quite elegant, Darwinian solution able to accommodate aspects of both Gibson's [34,35] theory of direct perception and Brunswik's [9,11] theory of probabilistic functionalism. For empirical research demonstrating the utility of drawing simultaneously on both Brunswikian and Gibsonian theory see Kirlik [55,53,54,56] and Davids, Button, Araujo, Renshaw & Hristovski [17]. Recent Brunswikian research (e.g., Gigerenzer & Engel [36]; Gigerenzer & Goldstein [37]; Gigerenzer & Selten [40]; Gigerenzer et al [41]) is extending this approach in creative directions.…”
Section: Integrationmentioning
confidence: 99%
“…Other studies have also shown that the analysis of the dynamics of a single variable could reflect the global dynamics of an entire neurobiological system (e.g., Vereijken et al, 1997) and of the dyadic interactions between team games players (e.g., Passos et al, 2008). Previous studies on the dynamics of decision making behaviours in sport have been mainly focused on team sports, typically in 1vs1 interactions (e.g., Araújo, Davids, Bennett, Button, & Chapman, 2004;Davids et al, 2006), or in dyadic sports (e.g., squash by McGarry et al, 2002). This study advanced understanding by investigating interactions of multi-player sub-phases in field invasion team games.…”
Section: Collective Behaviour Conveyed By Distance Gained Dynamicsmentioning
confidence: 99%
“…Team sports can be regarded as social neurobiological systems in a complementary perspective that integrates each performer's central nervous system, bodyeenvironment interactions (biological e or interactions of a biological movement system and its environment) in an interpersonal social system (Davids, Araújo, Shuttleworth, & Button, 2003;Keil, Holmes, Bennett, Davids, & Smith, 2000;Kelso, 2009;Neisser, 1994;Newell, 1986;Van Gelder & Port, 1995). Social neurobiological systems are important to study because movement behaviour of each individual performer may be considered an emergent property of the continuous interactions of biological animated systems and the environment in goal-directed behaviours (Davids, Araújo, Shuttleworth, & Button, 2003;Davids, Button, Araújo, Renshaw, & Hristovski, 2006;Kelso, 2009;Newell, 1986). In social neurobiological systems, a relevant concept to understand is self-organization (Kelso, 1995(Kelso, , 2009).…”
Section: Introductionmentioning
confidence: 99%